The clinical epidemiology study of orofacial clefts and genome-wide linkage analysis among large extended families with nonsyndromic orofacial cleft - Sulaiman, Wan Azman Wan (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2016)
Non-syndromic oral clefts is one of the most common birth defect in the world. Approximately 70% of cleft lip and/or palate (CLIP) cases are non-syndromicand it varies among races and geographic region. In a fist phase, a descriptive epidemiological study was carried out in all CLIP cases registered in Hospital Universiti Sains Malaysia (HUSM) from year 1997-2013. Large extended family with more affected family members was identified through database for the second phase experimental work. In second phase, genome-wide linkage analysis was carried out to the 8 selected large extended families using microarray platform and validated by copy number variation (CNV) analysis. The demography data analysis has been done for a cleft lip and/or palate in Kelantan and certain regions in Malaysia including Selangor, Johor, Terengganu and Pahang. The total of this cleft patient is up to 550 patients with 274 cases for male and 276 cases of female. The study found that 4b4 total cases in Kelantan, 74 cases In Terengganu , 16 cases in Pahang, Johor and Kedah with 2 and 1 cases only. A preliminary study has detected IRF6 mutations. Seven variants, including five known (c.-75-4A>G, c.-73T>C, c.459G>T 5, c.820G>A, and c.1060+37C>T) and two novel (c.-75-23G>C and c.1380G>T), were found. A significant nonparametric linkage (NPL) score and suggestive NPL and logarithm of the odds (LOD) scores were attained from family 50, 58, 99 and 100 under autosomal recessive mode. Several linkage intervals were attained. The study of the demography data using a statistical data analysis, divided cleft into several types. There are Unilateral cleft lip and palate (UCLP), Unilaterel cleft lip (UCL), Bilateral cleft lip and palate (BCLP), Bilateral cleft lip (BCL) and Cleft palate (CP). From the result, the total of the cleft study in the HUSM, report with 550 of cleft cases with total of UCLP cases is 227, UCL with 68 cases, BCLP with 116 cases, only 3 cases for BCL and CP with 136 cases. A comprehensive investigation of the candidate genes in orofacial clefts is warranted. IRF6 variants could, at best, contribute to clefting as part of a complex inheritance pattern, with both additional genes and environmental factors having a role. The findings of LPHN2 at 1 p31, PVRL3 at 3q13.3 SA TB2 at 2q31.1 q35 would shed more light on the disease mechanism that has been discovered through genome-wide linkage analysis.